2021
DOI: 10.3390/ani11030902
|View full text |Cite
|
Sign up to set email alerts
|

Thai Native Chicken as a Potential Functional Meat Source Rich in Anserine, Anserine/Carnosine, and Antioxidant Substances

Abstract: This study identified anserine and anserine/carnosine in chicken breast of Thai native chicken (TNC; 100% Thai native), Thai synthetic chicken (TSC; 50% Thai native), and Thai native crossbred chicken (TNC crossbred; 25% Thai native) compared with commercial broiler chicken (BR; 0% Thai native) using nuclear magnetic resonance (NMR) spectroscopy and the effect on antioxidant activity using 2,2-diphenyl-1-picrylhydrazyl assay (DPPH). We conducted experiments with a completely randomized design and explored prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…Additionally, the antioxidant properties of TSC, in terms of anserine and anserine/carnosine, were comparable with those of TNC but higher than in a commercial broiler chicken [3]. However, in our previous studies, we realized that, regardless of whether the native fraction was decreased (i.e., 25% Thai native genetics), the potential bioactive ingredients did not differ from 50% in TSC but were higher than those in commercial broilers [3]. Therefore, it was hypothesized that chickens with 25% Thai native genetics would have better growth performances than those that were 50% Thai native.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…Additionally, the antioxidant properties of TSC, in terms of anserine and anserine/carnosine, were comparable with those of TNC but higher than in a commercial broiler chicken [3]. However, in our previous studies, we realized that, regardless of whether the native fraction was decreased (i.e., 25% Thai native genetics), the potential bioactive ingredients did not differ from 50% in TSC but were higher than those in commercial broilers [3]. Therefore, it was hypothesized that chickens with 25% Thai native genetics would have better growth performances than those that were 50% Thai native.…”
Section: Introductionmentioning
confidence: 74%
“…The cumulative egg production of TSC was 182 eggs, higher than TNC cumulative egg production of 176 eggs [14]. Additionally, the antioxidant properties of TSC, in terms of anserine and anserine/carnosine, were comparable with those of TNC but higher than in a commercial broiler chicken [3]. However, in our previous studies, we realized that, regardless of whether the native fraction was decreased (i.e., 25% Thai native genetics), the potential bioactive ingredients did not differ from 50% in TSC but were higher than those in commercial broilers [3].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Bal has also been detected in the muscles of cetaceans, such as sperm whales, blue whales, and fin whales, and in snakes, such as sea snakes and cobras [ 1 ]. In contrast to the few studies on the functionality of Bal, many studies on the antioxidant activities of Car and Ans have been published [ 3 , 4 , 5 , 6 , 7 , 8 ]. Human trials have demonstrated that supplementation with Car reduces plasma soluble transferrin receptor and serum resistin concentrations in obese subjects [ 9 , 10 ], similar to in vitro studies.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, meat of native chicken has lower contents of fat and cholesterol ( Jaturasitha et al, 2016;Bungsrisawat et al, 2018). Thai native and Thai native crossbred chicken showed high anserine anserine/carnosine antioxidant substances carcass and meat quality yields (Charoensin et al, 2021). Eggs are considered rich sources of protein and iron (Kusum et al, 2018).…”
Section: Introductionmentioning
confidence: 99%